Stock Market Reaction to The Announcement of 2022 Fuel Price Increase on JII-30 - Muhammad Wafa Zidniilman; Vietha Devia (Universitas Airlangga, 2023)
ABSTRACT The growth of investors in the capital market always increases every year. The growth of investors in the capital market based on the Indonesian Central Securities Depository (KSEI) increased by 15.96% in 2022. As an investor, of course, the role of information is taken into account in making investments. The announcement of the fuel price increase is one of the available information and can be used as a reference in determining investment decisions. This study aims to determine the response of Jakarta Islamic Index 30 (JII-30) investors to the price increase (BBM) by observing the difference in abnormal returns and trading volume activity before and after the announcement of the 2022 fuel price increase. This research is quantitative and uses the event study method. Based on the research obtained results that between before and after the event occurred, abnormal returns and Trading Volume Activity (TVA) there was no significant difference influenced by the increase in fuel prices. This shows that there is no investor response to the announcements of the fuel price increase. Investors can be wiser and more careful in responding to announcement information and making decisions that will be applied in investing and investors can sort out in advance related announcements and issues as a consideration before making decisions in investing. Keywords: Abnormal Return, Stock Liquidity, Trading Volume Activity, Event Study. ABSTRAK Pertumbuhan investor di pasar modal selalu meningkat dalam setiap tahunnya. Pertumbuhan investor di pasar modal berdasarkan Kustodian Sentral Efek Indonesia (KSEI) meningkat sebesar 15,96% di tahun 2022. Sebagai seorang investor, tentunya peran informasi adalah salah satu yang diperhitungkan dalam melakukan investasi. Pemberitaan kenaikan harga BBM merupakan salah satu informasi yang tersedia dan dapat dijadikan acuan dalam menentukan keputusan dalam berinvestasi. Penelitian ini bertujuan untuk mengetahui respon investor Jakarta Islamic Index 30 (JII-30) pada kenaikan harga (BBM) melalui pengamatan terhadap perbedaan abnormal return dan juga trading volume activity antara sebelum dan sesudah pemberitaan kenaikan harga Bahan Bakar Minyak (BBM) 2022. Penelitian ini merupakan penelitian kuantitatif dan mengunakan metode event study. Berdasarkan penelitian diperoleh hasil bahwa antara sebelum dan setelah event terjadi, abnormal return dan Trading Volume Activity (TVA) tidak terdapat perbedaan signifikan yang dipengaruhi oleh kenaikan harga BBM. Hal tersebut menunjukan tidak adanya respon investor terhadap pemberitaan kenaikan harga BBM. Investor dapat lebih bijak dan cermat dalam menyikapi pemberitaan informasi dan mengambil keputusan yang akan diterapkan dalam berinvestasi serta investor dapat memilah terlebih dahulu terkait berita dan isu sebagai pertimbangan sebelum mengambil keputusan dalam berinvestasi. Kata Kunci: Abnormal Return, Likuiditas Saham, Volume Aktivitas Perdagangan, Event Study.